Avaliação do estado de conservação de Butia exilata e o impacto dos agrotóxicos na dinâmica de vida das abelhas solitárias - Wons, Fernando (2020)
The Butia exilata palm is endemic to the northwest of Rio Grande do Sul and is Critically Endangered (CR). As it is a relatively new species for science, information on reproduction, population structure, occurrence and distribution is still scarce. This information is important to support any species conservation effort. Part of the B. exilata pollinator species are solitary bees, which are at serious risk due to several factors, including the use of pesticides. About 423.66 km were covered in the region of possible occurrence of the species. All possible individuals of B. exilata sighted were identified, analyzed, photographed and georeferenced. The Geospatial Conservation Assessment Tool - GeoCAT was used to calculate the Occurrence Extent (EOO) and Occupation Area (AOO) of the species. A systematic sampling was carried out within the limits of the Papagaio Charão State Park - PEPC, over an area of 322.89 hectares, historically occupied by grassland, with 25 plots of 20x20 (400 m²). Images from Landsat 7/NASA, from 2003 and Landsat 8/NASA from 2020, were used for the elaboration of the Normalized Difference Vegetation Index (NDVI) maps. In the city of Pontão/RS, on the sides of the ERS 324 highway, observation of pollinators and fruit collection were made. As a result it was determined the Extent of Occurrence (EOO) of B. exilata in 627,072 km² and the Occupation Area (AOO) in 160,000 km², the latter ten times greater than previously thought. A population of approximately 29,000 individuals was discovered within the PEPC, but the area of grassland decreased from 227.56 hectares in 2003 to 43.621 hectares in 2020, as a result of forest regeneration. Only 29.37% of individuals within the PEPC were reproducing; in contrast to 97.16% of individuals located on the side of roads. Six genera of bees and wasps were observed visiting the flowers, being Augochlora sp. and Ceratina sp. genera of solitary bees and Apis mellifera (Linnaeus, 1758), Paratrigona sp., Polybia sp. and Tetragonisca sp. genera of social bees. Despite extending EOO and AOO, data on habitat loss, reproduction and fragmentation of the environment reinforce the species classification in the Critically Endangered (CR) category. Concomitantly, a systematic review of the effects of pesticides on the life of solitary bees was carried out. The research was carried out in the following databases: Scopus, ScienceDirect, PubMed, Wiley and Web of Science, with the following keywords and their combinations: “assessment”, “ecotoxicology”, “effect”, “exposure", "insecticides", "pesticide", "risk” and “solitary bee". Two hundred and twenty nine (229) articles were found, of which 13 were selected. The researchers tested the effects of 18 pesticide formulations, mainly organophosphates and neonicotinoids, on four species of solitary bees: Osmia bicornis, Megachile rotundata, Osmia cornuta and Osmia lignaria. The most widely used pesticide was the neonicotinoid Imidacloprid. Most of the insecticide formulations tested negatively affected at least one of the following categories: Abundance, Food, Longevity, Memory, Mortality, Nest Recognition and Reproduction. According to the criteria used, the review did not result in species found pollinating B. exilata.